Second Generation Biofuel – An Alternate Source of Energy: Life Sciences-Biotechnology for Prospective Medical Science - R. Devika; M. Subathra; J. Madhusudhanan; Rajesh; UditSagar (International Journal of Life Science and Pharma Research, 2022)
The use of fossil fuels in the current situation has been increased. These fossil fuels do not come under the category of sustainable sources due to its depleting nature. Fossil fuels also pollutes the environment by increased emission of Greenhouse Gases (GHG). In order to produce an alternate renewable energy and to reduce the percentage of environmental pollution caused, many technologies like solar energy, tidal energy, wind energy etc. came into existence. But all these forms of energy can be produced in terms of electricity. To meet the increasing fuel demand, renewable biofuels came into the field where biomasses are utilized to produce biofuels. Second generation renewable biofuels are produced from conventional plant sources with higher oil content whose efficiency is determined by the amount of Green House Gases (GHG) emitted and the life cycle cost whether positive, neutral or negative. High yielding energy crops such as sugarcane, corn, switchgrass, wheat etc. are subjected to various processes / fermentation to yield biofuels like bioethanol, biobutanol, biohydrogen, biodiesel etc. The US and Brazil are replacing the demand for gasoline with around 15% of bioethanol and it has a higher octane rating, increased engine’s compression ratio, increased thermal efficiency and ultimately reduces atmospheric pollution emissions. In future biofuels will be recognized as alternative fuel in transportation, energy generation, heat producer, charging electronics, environmental friendly cleaners, cooking, lubricants, adhesives etc. This review provides a brief outline about the second generation biofuels which would serve as an alternative energy in the near future.